Does the Recent Success of Some OECD Countries in Lowering their Unemployment Rates Lie in the Clever Design of their Labour Market Reforms? - Michèle Belot; Jan C. van Ours (Institute for the Study of Labor (IZA), 2000)
The development of the unemployment rate differs substantially between OECD countries. In recent years some countries experienced a mild increase, other countries had a stable unemployment rate, while there are also 'successful' countries in which the unemployment rate decreased a lot. A common feature of the successful countries is that they implemented a comprehensive set of institutional reforms. In this paper we present a theoretical and empirical framework to investigate how unemployment is affected by different labour market institutions (LMI) such as labour taxes, unemployment benefits, employment protection, union bargaining power and (de)centralisation of bargaining. We argue that complementarities between LMI can be exploited to improve labour market performance. In our empirical analysis of annual data over the period 1960-1995 of eighteen OECD countries we show that interactions between LMI are indeed important.
Keywords: J68; E24; 330; OECD; unemployment; institutions; complementarities; reforms; Arbeitsmarktpolitik; Arbeitsmarktflexibilisierung; Wirtschaftspolitische Wirkungsanalyse; Arbeitslosigkeit; Schätzung; OECD-Staaten